Ensuring price stability in post-crisis Asia lessons from the recovery - Filardo, Andrew J. 1962- (BIS working papers, 2012)
Asian central banks have adopted monetary policy frameworks over the past decade that have, by and large, worked well both to ensure price stability during the pre-crisis period and to navigate the shoals during the recent international financial crisis. Inflation concerns in recent years nonetheless raise the possibility that existing monetary policy frameworks in Asia may be contributing to procyclical inflation swings. Three particular aspects of the policy environment are highlighted. They include the approach of monetary policy to commodity price cycles, to the uneven global recovery and to the new financial stability mandates.